Effect of Lactobacillus casei shirota strain probiotic beverage on the release of chromium ions in stainless steel brackets - Fransiska, Aria; Yohana, Nelvi; oktafiani, Meli (Padjadjaran Journal of Dentistry, 2023)
AbstractIntroduction: Stainless steel brackets are often used in orthodontic treatment. Chromium is one of the stainless steel bracket elements that increases corrosion resistance. Chromium ions’ release can cause allergic reactions. Acidic pH due to food and drink consumption can cause corrosion and the release of ions. One of the most widely consumed acidic pH drinks is the Lactobacillus casei Shirota strain probiotic because it provides health benefits. The purpose of this study was to analyze the effect of the Lactobacillus casei Shirota strain probiotic beverage on the release of chromium ions in stainless steel brackets. Methods: This study was laboratory experimental research with a posttest only control group design. The number of samples was 10 for two groups. The bracket was immersed in artificial saliva as the control group and in the probiotic drink Lactobacillus casei Shirota strain as the treatment group. After 18 hours and 15 minutes of immersion, in an incubator at 37°C, the immersion solutions were tested using Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) to determine the release of chromium ions. The results of the study were analyzed using an independent t-test. Results: The average chromium ion release in the control group was 7.63 ppm, while in the treatment group it was 7.87 ppm. The results of the independent t-test showed a significant difference (p<0.05). Conclusion: The probiotic beverage Lactobacillus casei Shirota strain increased the release of chromium ions in stainless steel brackets. It is greater than that immersed in artificial saliva. The value of chromium ion release obtained was still below the average daily intake of chromium.